1999
DOI: 10.3171/foc.1999.7.4.1
|View full text |Cite
|
Sign up to set email alerts
|

Localization of hand motor activation in Broca's pli de passage moyen

Abstract: Object The object of this study was to identify a reliable surface landmark for the hand motor area and to demonstrate that it corresponds to a specific structural component of the precentral gyrus. Methods Positron emission tomography (PET) activation studies for hand motor function were reviewed in 12 patients in whom magnetic resonance imaging results were normal. Each patient performed a hand opening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
1
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 24 publications
(44 reference statements)
2
43
1
2
Order By: Relevance
“…Finally, our data confirmed previous work that the representation of the hand in the primary motor cortex (area 4) is located in the precentral knob (Broca, 1888;Yousry et al, 1997;Boling et al, 1999), which is found in the depth of the central sulcus. Note that the location of the premotor visuomotor hand conditional activity was anterior to the primary motor representation of the hand (indicated in green in all subjects in Figs.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Finally, our data confirmed previous work that the representation of the hand in the primary motor cortex (area 4) is located in the precentral knob (Broca, 1888;Yousry et al, 1997;Boling et al, 1999), which is found in the depth of the central sulcus. Note that the location of the premotor visuomotor hand conditional activity was anterior to the primary motor representation of the hand (indicated in green in all subjects in Figs.…”
Section: Discussionsupporting
confidence: 81%
“…knob" (Yousry et al, 1997), also known as Broca's pli de passage moyen (Broca, 1888;Boling et al, 1999), in the left hemisphere in each individual subject [average MNI coordinates (x, y, z): Ϫ37.1 Ϯ 6.7 SD, Ϫ25.6 Ϯ 5.4 SD, 62.5 Ϯ 5 SD] (Figs. 2-4, 5d; Table 2).…”
Section: Primary Motor Cortex Hand Activity In the Central Sulcusmentioning
confidence: 99%
“…In clinical practice several paradigms are used to identify the sensory and motor areas (Lee, et al 1998;Boling, et al 1999) and language-related areas (Binder, et al 1997;FitzGerald, et al 1997;Benson, et al 1999;Fernandez, et al 2001). Some batteries have been developed for neurosurgical planning that include multiple, overlapping tasks for motor and language mapping (Tomczak, et al 2000;Heilbrun, et al 2001;Haberg, et al 2004), and one battery includes tasks for motor, sensory and language mapping (Hirsch, et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The precentral gyrus, in addition to its superior and inferior connections with the postcentral gyrus via the superior (paracentral lobule) and inferior frontoparietal fold (subcentral gyrus, or rolandic operculum), is usually also connected to the postcentral gyrus via a transverse gyrus that lies along the bottom of the central sulcus and constitutes the so-called Broca's medial frontoparietal pli de passage. 2,72 This fold is situated at the level of the middle knee of the precentral gyrus, which is itself normally situated at the level of the superior frontal sulcus, corresponding to the portion of the gyrus that functionally harbors the motor representation of the contralateral hand. Therefore, the superior frontal sulcus tends to point the way to the medial frontoparietal pli de passage, as well as to the middle knee of the precentral gyrus, with its respective motor representation of the hand.…”
Section: The Central Lobementioning
confidence: 99%
“…The well-known variability in cortical function 1,2,17,47,53,75 calls for the aid of cortical mapping techniques to precisely identify specific sites related to cortical function. Nevertheless, detailed knowledge of the structure and form of the cerebral sulci and gyri continues to be mandatory for neuroimaging as well as intraoperative guidance.…”
mentioning
confidence: 99%